The role and use of information communication technology to empower women : a literature review. - Amadhila, Helena Naitsuwe (2007)
This paper contains a review of the role and use of Information Communication Technology (ICT) in the empowerment of women by examining their participation in and usage of lCT. Findings from researches conducted in America and Asia, indicate that ICT plays a major role in women's lives as well as in the community at large. However, little or no attention has been paid to the role of ICT especially in Namibian communities. ICT is a catalyst for change agents and other stakeholders embarking on human capital development aiming to empower the community. Therefore, ICT should be integrated in the developmental progamme packages.